2021
DOI: 10.31234/osf.io/8xjzb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Systematic Review of Parenting in Singapore: Insights to the Culture-Specific Functions of Styles and Practices

Abstract: Cross-cultural studies on parenting have identified cultural nuances that may impact the form and functions of parenting styles and practices in different contexts. This systematic review is undertaken with the aim of identifying such nuances in an under-studied culture (Singapore), as a starting point to understand and compare the forms and functions of parenting in Asia and beyond. A review of 27 studies showed that optimal parenting styles and practices were associated with positive child development outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…Thus, Baumrind and Thompson (2002), affirm that the authoritative parenting style is the most encompassing way of raising successful children. Cheung (2021) also affirmed in the systematic review, the benefits of authoritative parenting style in children in Singapore which included gains in behavioural and social-emotional outcomes.…”
Section: Parenting Stylesmentioning
confidence: 78%
See 2 more Smart Citations
“…Thus, Baumrind and Thompson (2002), affirm that the authoritative parenting style is the most encompassing way of raising successful children. Cheung (2021) also affirmed in the systematic review, the benefits of authoritative parenting style in children in Singapore which included gains in behavioural and social-emotional outcomes.…”
Section: Parenting Stylesmentioning
confidence: 78%
“…A local systematic review on parenting in Singapore (Cheung, 2021) found that like research done in the western countries, the authoritarian style is associated with a decreased level of confidence and esteem. In addition, this style of parenting was also correlated with adjustment issues, aggressive and defiant behaviours in children in Singapore.…”
Section: Parenting Stylesmentioning
confidence: 91%
See 1 more Smart Citation
“…Apart from that, Asian culture values respect for authority and elders; thus, parents are inclined to use more orders and try to control their children’s behaviour more openly than Western parents (Russell et al, 2010). Southeast Asian parents tend to use authoritarian parenting style and corporal punishment at home (Chan, 2018; Cheung & Lim, 2021). Though parental physical abuse is different from corporal punishment, past research revealed that individuals who experienced corporal punishment are at an increased risk of also having experienced parental physical abuse (Fréchette et al, 2015).…”
Section: Discussionmentioning
confidence: 99%